1998
DOI: 10.1177/01454455980223010
|View full text |Cite
|
Sign up to set email alerts
|

A Dual Process Model of Perfectionism Based on Reinforcement Theory

Abstract: This article begins with a brief review of the current literature on the structure and measurement of perfectionism. It is concluded from this review that two major types can be distinguished, a normal/healthy form and a pathological form. These two forms are then defined as positive and negative perfectionism and related directly to Skinnerian concepts of positive and negative reinforcement. The positive/negative distinction is then further elaborated on in terms of approach/avoidance behavior, goal differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
255
1
36

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(313 citation statements)
references
References 27 publications
21
255
1
36
Order By: Relevance
“…The reason is that the PANPS has shown problems with content validity and factorial validity. As regards content validity, the PANPS was designed to capture positive and negative consequences of perfectionism (Terry-Short et al, 1995) following Slade and Owens' (1998) dual process model of perfectionism based on reinforcement theory.…”
Section: Perfectionism Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason is that the PANPS has shown problems with content validity and factorial validity. As regards content validity, the PANPS was designed to capture positive and negative consequences of perfectionism (Terry-Short et al, 1995) following Slade and Owens' (1998) dual process model of perfectionism based on reinforcement theory.…”
Section: Perfectionism Dimensionsmentioning
confidence: 99%
“…Following the two-factor model of perfectionism (Stoeber & Otto, 2006), hope for perfection relates to the perfectionistic strivings aspects of physical appearance perfectionism whereas worry about imperfection relates to the perfectionistic concerns aspects. Furthermore, the two components can be understood from the perspective of Slade and Owens's (1998) dual model of perfectionism as approach-oriented (hope for perfection) versus avoidance-oriented (worry about imperfection).…”
Section: Physical Appearance Perfectionismmentioning
confidence: 99%
“…Research in both fields has also identified the importance of accounting for adaptive versus maladaptive dimensions of the constructs (Allport & Ross, 1967;Slade & Owens, 1998). When the constructs are compared using adaptive and maladaptive subdimensions, the relationship between perfectionism and religiosity can best be described by accounting for the subdimensions of the construct.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…This distinction has been supported by the multidimensional research and studies designed to test the positive and negative perfectionism theory. The Dual Process Model of Perfectionism made a distinction between the pursuit of success, excellence, approval, and satisfaction; and the avoidance of failure, mediocrity, disapproval, and dissatisfaction (Slade & Owens, 1998).…”
Section: Theoretical Debatementioning
confidence: 99%
“…Existen numerosas investigaciones que demuestran rasgos perfeccionistas desadaptativos vinculados al deporte (García-Fernández et al, 2016), contemplando que el miedo al fracaso crea en ellos una falta de diversión (Fiorese, Andrade y Lopes, 2013). Slade y Owens (1998) argumentaron que el Perfeccionismo Socialmente Prescrito (PSP) se relaciona con el miedo al fracaso, provocando la evitación de resultados negativos y el comportamiento basado en la motivación extrínseca. Sin embargo, a pesar de que el perfeccionismo ha sido considerado, generalmente, como un constructo desadaptativo, existen evidencias de algunas facetas que pueden llegar a considerarse positivas y gratas en algunos casos.…”
Section: Introductionunclassified